The clinical value of acupuncture combined with Wenjing decoction in treating primary dysmenorrhea in women—a systematic review and meta-analysis of randomized controlled trials - Zhao, Mei; Zhou, Fuhua; Qiu, Chunmei; Hu, Xiumei; Xie, Caiping; Wen, Lixin; Xu, Lianwei (Frontiers in Medicine, 2025)
ObjectiveTo systematically evaluate the clinical efficacy of combining acupuncture and Wenjing decoction for primary dysmenorrhea (PD) of cold congealing and blood stasis type, using the meta-analysis research methods, to provide references for clinical treatment.MethodsA randomized controlled trial (RCT) on the treatment of PD using Wenjing decoction with or without acupuncture was searched across multiple databases from 1 January 2000 to 1 March 2025. Outcome measurements included serum hormone levels, pain scores, uterine artery blood flow, and overall effectiveness rate. The quality of the studies included was assessed using the risk of bias tool. The methodological quality of the included studies was assessed with the Cochrane Collaboration tool. Review Manager 5.4 software was employed for quantitative synthesis, and funnel plots were utilized to evaluate potential reporting bias.ResultsA total of 11 RCTs with 1,024 patients with primary dysmenorrhea were included. Wenjing decoction combined with acupuncture in the treatment of PD has obvious advantages over the control group in improving the effective rate [relative risk (RR) = 1.24], [95% confidence interval (CI): (1.06, 1.42), I2 = 34%, p = 0.15], increasing the level of PGE₂ [mean difference (MD) = 5.9, 95% CI: (2.27, 9.52), I2 = 63%, p = 0.07], reducing the level of PGF2α [MD = −11.96, 95% CI: (−25.21, −1.28), I2 = 63%, p = 0.07], reducing pain score [−4.13, 95% CI: (−6.42, −1.84), I2 = 99%, p < 0.00001], improving uterine artery blood flow resistance index (RI) [MD = −0.09, 95% CI: (−0.12, −0.07), I2 = 18%, p = 0.27], and uterine artery blood flow pulsatility index (PI) [MD = −0.39, 95% CI: (−0.44, −0.33), I2 = 0%, p = 0.41]. The differences are statistically significant (p < 0.05).ConclusionThe combination of acupuncture and Wenjing decoction in the treatment of primary dysmenorrhea (PD) is superior to simple Western medicine treatment in reducing the level of prostaglandin F2 alpha (PGF2α), increasing the level of prostaglandin E2 (PGE2), decreasing the pain score, improving the resistance index (RI) and pulsatility index (PI) of uterine artery blood flow, as well as the total effective rate. However, the methodological quality of the studies included was undesirable, necessitating further verification with more well-designed and high-quality multicenter RCTs.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024623207.